2011
DOI: 10.1016/j.physe.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The quantum computational speed of a single Cooper-pair box

Abstract: The speed of computations is investigated by means of the orthogonality speed for a charged qubit interacting with a single cavity field prepared initially in a Fock state or Binomial state. We observe that the rate of the computational speed is related to the number of photons inside the cavity. Moreover, we show that the qubit-field coupling plays an opposite role, where the speed of computations is decreased as the coupling is increased. We suggest using the number of photons in the field as a control param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…13,18 Suppose that the gate capacitance C g is screened from the quantized radiation¯eld, and the system can be described by a two-level system with Hamiltonian. 20,22,26,27 …”
Section: The Modelmentioning
confidence: 99%
“…13,18 Suppose that the gate capacitance C g is screened from the quantized radiation¯eld, and the system can be described by a two-level system with Hamiltonian. 20,22,26,27 …”
Section: The Modelmentioning
confidence: 99%
“…The interaction of the single photon field with superconducting circuit to generate quantum bits is studied experimentally [1,2] and theoretically [3][4][5]. Wallraff et al have observed a strong coupling between the superconducting two-level system and a single microwave photon which prove the generation of qubits.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the single photon field with superconducting circuit to generate quantum bits is studied experimentally [15], [16] and theoretically [24], [25], [26]. Wallraff et al have observed a strong coupling and coherent between the superconducting two-level system with a single microwave photon which prove that the qubits is generated.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting entanglement in this system is quantified using different measures [24]. The optimum parameters of the system to be used in the quantum teleportation process [33], speed of computations [25] and dynamics of the coded information [26] are investigated. The dynamical properties of the interaction of the single cooper pair box with two cavity field is studied [34].…”
Section: Introductionmentioning
confidence: 99%